Web based healthy menu planner / Nursyairah Zainal Abidin - Zainal Abidin, Nursyairah (2020)
The aim for this research is to design and develop a web-based healthy menu planner that has the ability to suggest weekly menu with recipe based on individual calorie need with Malaysian local dishes. Software Development Life Cycle (SDLC) with waterfall model has been utilized as the methodology of this study. The waterfall model consists of five phases including analysis, design, implementation, testing and documentation. Persuasive Technology has been used as a guideline in designing this system. Few principles from Persuasive Technology was adapted during the design which are principle of tailoring, principle of tunneling and principle of suggestion. Functionality testing, heuristic evaluation, content expert review and user experience test were conducted during the study to evaluate the system. Functionality Testing was conducted to verify that all modules in the system function effectively and efficiently. The result from the UX Testing indicates that most of the users agree that the system is useful, effective and reliable and has a good value. Most of the users also would like to recommend this system to their friend and colleague. Suggestions from experts during the heuristic evaluation and content expert evaluation session were also taken into consideration and few refinements were made based on those recommendations. It is hoped that, by using this system, the users would be able to plan their weekly menu effectively. Then, it is also hoped that this system will motivate the users to eat healthy and thus will combat the obesity problem in our society and reduce diseases that are related to obesity.